The three bears and goldilocks (big book) - Langley, Jonathan (Collins Educational London, 1998)
Once upon a time, there were three bears who lived in a little house in a big wood. One morning they went out for a stroll in the woods and, while they were gone, a little girl arrived at their house. Finding no one there, she went inside!